2011
DOI: 10.1109/tsp.2010.2103069
|View full text |Cite
|
Sign up to set email alerts
|

Joint TDOA and FDOA Estimation: A Conditional Bound and Its Use for Optimally Weighted Localization

Abstract: Modern passive emitter-location systems are often based on joint estimation of the time-difference of arrival (TDOA) and frequency-difference of arrival (FDOA) of an unknown signal at two (or more) sensors. Classical derivation of the associated Cramér-Rao bound (CRB) relies on a stochastic, stationary Gaussian signal-model, leading to a diagonal Fisher information matrix with respect to the TDOA and FDOA. This diagonality implies that (under asymptotic conditions) the respective estimation errors are uncorrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 18 publications
1
65
0
Order By: Relevance
“…But in Appendix B.4 it is shown that the null space of I θ is not empty and so it is not invertible. This is because the log-likelihood function is not uniquely defined by the model in (23). To eliminate the over parameterization we use the following transformations.…”
Section: B11 Signal Unknown With Unknown Transmission Timementioning
confidence: 99%
See 2 more Smart Citations
“…But in Appendix B.4 it is shown that the null space of I θ is not empty and so it is not invertible. This is because the log-likelihood function is not uniquely defined by the model in (23). To eliminate the over parameterization we use the following transformations.…”
Section: B11 Signal Unknown With Unknown Transmission Timementioning
confidence: 99%
“…Stein [9] on the other hand modeled the signal as deterministic but unknown and derived the MLE for the differential delay and Doppler for a two sensor case. Under similar assumptions for the signal, Yeredor and Angel [23] have derived the CRLB for the TDOAs. After the TDOAs are estimated they are used to estimate the location of the source [24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of time, frequency and phase shifts estimation in dual-channel systems has been extensively studied in the literature, see [6][7][8][9][10][11][12]. An estimator for TDOA, phase and discrete Doppler shifts using Gaussian random signals was proposed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…An estimator for TDOA, phase and discrete Doppler shifts using Gaussian random signals was proposed in [7]. A signal model with TDOA, arbitrary Doppler shifts, and random phase using unknown deterministic signals was analyzed in [8]. In these papers and in a number of TDOA/FDOA localization related papers such as [10], the carrier phase of arrival (CPOA) term was modeled as a part of an unknown or random phase term or complex attenuation.…”
Section: Introductionmentioning
confidence: 99%